The generalized coefficients of earth pressure: A unified approach - Pantelidis, Lysandros (My University, 2019)
This paper offers an extension of Cauchy's first law of motion to deformable bodies with internal resistance with application to earth pressures. In this respect, a unified continuum mechanics approach for deriving earth pressure coefficients for all soil states, applicable to cohesive-frictional soils and both horizontal and vertical pseudo-static conditions is proposed. Adopting Jaky's (1944) sand heap hypothesis, modified suitably to accommodate the needs of the present research, the analysis led to generalized, yet remarkably simple in form, expressions for the "at rest", active and passive earth pressure coefficients. The validity of the proposed coefficients is strongly supported by the fact that, under static conditions they are transformed into the well-known Rankine's expressions for cohesive-frictional soils for the active and passive state. Comparisons with widely used solutions (e.g., Rankine's and Mononobe-Okabe's), design code practices (Eurocode 8-5; AASHTO), and results from centrifuge tests further support the validity of the proposed coefficients. In the framework of the present work, analytical expressions for the calculation of the depth of neutral zone in the state "at rest", the depth of tension crack in the active state, the required wall movement for the mobilization of the active or passive state, as well as the mobilized shear strength of soil (for all states) are also given. Finally, following the proposed approach, the earth pressure can be calculated for any intermediate state between the state "at rest" and the active or passive state when the allowable wall movement is known.
Keywords: Jaky’s coefficient of earth pressure at rest; Cauchy’s first law of motion; Pseudo-static analysis; Mobilized shear strength of soil; Active earth pressure coefficient; Passive earth pressure coefficient